Interaction proxemics and image use in neurosurgery - Mentis, Helena; O'Hara, Kenton; Sellen, Abigail; Trivedi, Rikin (Proceedings of CHI 2012, 2012)
Within medical settings there is a growing interest in exploring touchless interaction technologies. The primary motivation here is to avoid contact during interaction so as to maintain asepsis. However, there is another important property of touchless interaction that has significant implications for their use within such settings – namely that interaction behaviour is spatially distal from the device being interacted with. To further understand these implications we present fieldwork observations of work practice in neurosurgery theatres. Drawing on the notion of interaction proxemics and the theory of F-formations, our analysis articulates the spatial organization of collaborative work practices and interaction in these settings. From this understanding of spatial practices, we discuss opportunities and difficulties relating to the design of touchless interaction technologies for these settings.